PENGARUH BAHAN BAKAR PREMIUM, PERTAMAX, PERTAMAX PLUS DAN VARIASI RASIO KOMPRESI TERHADAP KADAR EMISI GAS BUANG CO DAN HC PADA SUZUKI SHOGUN FL 125 SP TAHUN 2007 - Winarto, Eko (Jurnal Nosel, 2014)
The purpose of this research: (1) Investigated the motorcycle exhaust emissions Suzuki Shogun FL 125 SP in 2007 used premium, pertamax,and pertamax plus. (2) Investigated the motorcycle exhaust emissions Suzuki Shogun FL 125 SP in 2007 used variation of compression ratio. (3) Investigated the motorcycle exhaust emissions Suzuki Shogun FL 125 SP in 2007 used interaction premium, pertamax, pertamax plus, and variation of compression ratio. Based on this researchcan be concluded: (1) The measurement premium fuel produced the lowest emission in CO 3.884% by 9.1:1 compression ratio and the the lowest exhaust gas emission levels in 168 ppm by 9.1:1 compression ratio. (2) The measurement pertamax fuel produced the lowest exhaust gas emission levels in CO 3.237% by 9.5:1 compression ratio and the the lowest exhaust gas emission levels in 210 ppm by 9.5:1 compression ratio(3) The measurement pertamax plus fuel produces the lowest exhaust gas emission levels in CO 2.615% by 10.2:1 compression ratio and the the lowest exhaust gas emission levels in 237 ppm by 9.5:1 compression ratio